An impulse UWB patch antenna with integrated bandpass filter - Badjian M.H.; Chakrabarty C.K.; Hock G.C.; Devkumar S. (2023)
An Ultra wideband patch antenna is tested in this paper for Impulse UWB applications. The IJWB patch antenna is integrated with UWB bandpass filter of desired operating frequency range. The design is on FR-4 substrate with dielectric constant of 4.4 and thickness of 1.6 mm. Impulse performance and angle of operation for such antenna are shown. 2008 IEEE.